Africon 2015 2015
DOI: 10.1109/afrcon.2015.7332017
|View full text |Cite
|
Sign up to set email alerts
|

Towards a conceptual framework for pledging sustainable e-Government success: The case of G2G in Ethiopia

Abstract: Sustaining successful e-government initiatives is of paramount importance for governments of developing countries. However, extant literature indicate that: (1) failure of e-government initiatives in those countries is very high and this demonstrates that the issue is challenging and poorly understood; and (2) sustainability aspect of e-government initiatives is a neglected topic and calls to extend e-government research beyond success. This research, thus, tries to explore the potential relationship between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 15 publications
(21 reference statements)
0
25
0
Order By: Relevance
“…The major global issues related to the E-Governance development to achieve the sustainable development goals (SDG) are recognized as cybersecurity, digital divide and transformation of government processes (United Nations, 2018). There are several challenges existing in implementing sustainable E-Governance in developing countries but there is little research on how to address these challenges (Lessa et al, 2015). Limited technical support and institutional capability, lack of awareness among top management and stakeholders, lack of skills, poor administrative relationship among stakeholders, lack of leadership and dependence on external assistance obstruct developing nations from successfully implementing the E-Governance (Dzhusupova et al, 2011;Kalsi and Kiran, 2015;Lessa et al, 2015).…”
mentioning
confidence: 99%
“…The major global issues related to the E-Governance development to achieve the sustainable development goals (SDG) are recognized as cybersecurity, digital divide and transformation of government processes (United Nations, 2018). There are several challenges existing in implementing sustainable E-Governance in developing countries but there is little research on how to address these challenges (Lessa et al, 2015). Limited technical support and institutional capability, lack of awareness among top management and stakeholders, lack of skills, poor administrative relationship among stakeholders, lack of leadership and dependence on external assistance obstruct developing nations from successfully implementing the E-Governance (Dzhusupova et al, 2011;Kalsi and Kiran, 2015;Lessa et al, 2015).…”
mentioning
confidence: 99%
“…Most of the e-governance research studies focuses on e-governance’s immediate success and ignore sustainability indicator of e-governance success (Larsson and Grönlund, 2014; Lessa et al , 2015). However, it is important to focus on the long-term success of e-governance.…”
Section: Discussionmentioning
confidence: 99%
“…The present research is aimed at investigating the strategic role of reengineering to ensure the implementation of future-oriented and sustainable e-governance by developing the core competencies. The literature indicated that the notion of future-oriented e-governance is nascent; therefore, literature lacks the model and discussion on how to achieve the same (Larsson and Grönlund, 2014, 2016; Lessa et al , 2015). When such a situation exists, it is recommended to use mixed method research, which is a collection of both qualitative and quantitative research methods, to develop a holistic understanding of a phenomenon (Sharma and Mishra, 2017; Venkatesh et al , 2013).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations